Usulan Perencanaan Tata Letak Gudang Produk Jadi dengan Menggunakan Metode Muther's Systematic Layout Planning dan Dedicated Storage - William Kemala; Gidion Karo Karo (Universitas Bunda Mulia, 2017)
The purpose of this study is to obtain a warehouse layout design along with the laying of each finished product shelves, making it easier and speed up the process and handle the product. The method used to design the warehouse layout is Muther's Systematic Layout Planning (SLP) by creating a diagram ARC and diagrams ARD. While the method used for the laying of each item to the shelves using the Dedicated Storage by calculating the needs of the area required, the distance of movement of goods and the amount of throughput (activities) that occur in the warehouse. The result from this study is the re-design layout that able to perform the process faster and orderly. While at the laying of goods also gained total slots required is 48 slots, categorized into 24 slots for items finished products by the brand SUPREME and 24 slots for items with the brands Eterna finished product. The number of pallets needed as many as 48 pallets. Total activity is 28 events for all goods.Keywords: Muther's Systematic Layout Planning, Warehouse Design, Pallet